Amorphophallus calladoi (Araceae), a new species from Luzon Island, Philippines - Bustamante, Rene Alfred Anton B.; Tamayo, Maverick N.; Collantes, John Paul; Pelser, Pieter B. (Phytotaxa, 2026)
A new species of Amorphophallus from Luzon Island, Philippines is here described. It is unique among Amorphophallus species in having a combination of the following characters: a ca. 1:2 peduncle to spathe ratio, a spreading and broadly triangular spathe with a deep and distinct constriction, a rugose appendix, stamens with rounded pores, and a trilobed stigma. A discussion on other closely related species is presented. We here provisionally assess this species as data deficient (DD) following IUCN guidelines pending an assessment of its populations in the wild. An identification key to Philippine species of Amorphophallus with rugose appendices is also provided.